Efikasi Formulasi Granular Kombinasi Trichoderma sp. dan Ekstrak Daun Bandotan terhadap Sclerotium rolfsii pada Porang (Amorphophallus oncophyllus) - Raniah, Nabilla Nur; Nirwanto, Hery; Suryaminarsih, Penta (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Amorphophallus oncophyllus is a tuber plant that is beneficial for various industrial sectors, but in its cultivation, it is often affected by the pathogen Sclerotium rolfsii, requiring control measures. Control efforts can be carried out using a combination of the biological agent Trichoderma sp. and the plant pesticide made from bandotan leaf extract. The combined control application can be formulated in a solid granular form. Method: This research was conducted both in vitro and in vivo. In vitro, a Completely Randomized Design (RAL) was used with the combination of Trichoderma sp. and bandotan leaf extract, divided into four levels: 0% (TB0), 5% (TB5), 10% (TB10), and 15% (TB15). In vivo, a 2-factor RAL was applied. The first factor was the concentration of the rice flour carrier material in four levels: 0% (B1), 25% (B2), 50% (B3), and 75% (B4). The second factor was the storage duration of the granular formulation, consisting of 0 weeks (M1), 3 weeks (M2), and 5 weeks (M3). Result: The study's results showed that the granular combination of Trichoderma sp. and 10% bandotan leaf extract reduced S. rolfsii infection by 64.25% and stimulated the growth of porang plant height. Conclusion: The treatment with the granular combination of Trichoderma sp. and 10% bandotan leaf extract, adding 25% rice flour and a storage period of 0-3 weeks, showed the best effect on the porang plant seedlings.